DECODING CONNOTATIVE MEANING IN THREE (3) PROVIDER ADVERTISEMENT KEBEBASAN EPISODE - NURNASTITI, DESY SINTA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Semiotics, Codes, Connotative Meaning, Three (3) provider, Advertisement.This study analyzes the codes and connotative meaning in Three (3) provider advertisement kebebasan episode. Three (3) provider is one of provider which is distributed in Indonesia. In this research, the writer analyzed the codes and connotative meaning used in Three (3) Provider in order to understand the deeper meaning of this advertisement. The research problems are: 1) What kind of codes used in Three (3) Provider kebebasan episode, 2) What are the connotative meaning found in Three (3) provider kebebasan episode. The main theory used in this study are tripartite framework from Chandler (2007) and the order of signification from Barthes (1957).This study uses qualitative approach since the writer tries to analyze the visual and verbal elements of Three (3) Provider advertisement kebebasan episode. The data of the study are video advertisement containing codes and connotative in Three (3) Provider advertisement kebebasan episode.The results of this study reveal that Three (3) provider advertisement kebebasan episode contains codes and connotative meaning to deliver message about freedom in society and insinuate other provider implicitly at the same time. Three codes proposed by Chandler are applied in the advertisement. The codes which are found are social codes (verbal language, bodily codes, commodity codes); textual codes (genre, rhetorical and stylistic code; mass media code) and interpretative codes (perceptual code). In the finding, all of the scenes of Three (3) Provider advertisements kebebasan episode have connotative meanings because all of them contain both images and utterances that have hidden messages.To sum up, Three (3) provider uses codes and connotative meaning to deliver the deeper message about freedom in society and insinuate other provider implicitly. Further, the readers can get additional information related to the codes and connotative meaning. The writer suggests for the next researchers who are interested in the semiotics to take data from other sources like radio, newspaper, magazine, advertisement poster or novel poster. The future researcher can use theories from other experts as well.